“Existimos”: Health and social needs of transgender men in Lima, Peru - Reisner, Sari L.; Silva-Santisteban, Alfonso; Salazar, Ximena; Vilela, Jesse; D’Amico, Lynne; Perez-Brumer, Amaya (PLOS ONE, 2021)
Background The health of transgender men (trans men)–individuals who identify as men and were assigned a female sex assigned at birth–is overlooked globally. This mixed-methods exploratory study sought to understand the lived experiences, health, and social needs of trans men in Lima, Peru to bring visibility to specific health needs and inform responsive and holistic public health efforts. Methods Between July 2016-January 2017, 46 trans men in Lima, Peru participated in a mixed-methods study. Four focus group discussions were conducted, complemented with 10 one-on-one interviews to explore in-depth issues that arose in groups. Two individuals participated in both a focus group and an interview. All participants completed a brief survey assessing sociodemographic characteristics and experiences with healthcare, mental health, and stigma. Audio files were transcribed verbatim and analyzed using an immersion crystallization approach to identify themes. Results Participants had a mean age of 24 years (range 18–48). Trans men reported a lack of awareness and information among medical providers, avoidance of healthcare due to discrimination and maltreatment, an absence of public services for medical gender affirmation (hormones, surgeries), and unmet mental health needs. Trans men described health as multidimensional and influenced by social, economic, and legal contexts including family, school, employment and work, legal identity recognition, discrimination in public spaces, and peer support. Violence, stigma, and intersecting forms of oppression were described as limiting social and legal recognition of trans identity a central dimension of health. Peer support, often in an online environment, was described as important to resistance and well-being. Conclusions Findings demonstrate that the physical and mental health of trans men, as well as unmet needs for healthcare services, are influenced by a complex set of social, economic, and legal challenges due to the social exclusion of trans people in Peruvian society. Results are a call to action for stakeholders in Peru to guarantee the rights, health, and wellbeing of this community.